High-quality perovskite films via post-annealing microwave treatment - Sagar Jain (New Journal of Chemistry, 2019)
Crystalline quality of the perovskite film plays a key role in improving the optoelectronic properties and performance of planar perovskite hybrid solar cells (PSCs). In this work, a methodology employing post-annealing microwave treatment (MPAT) for fine tuning the crystallization of perovskite films is proposed. It is found that microwave induced electromagnetic waves results in the dipoles and ions to vibrate at high frequency in perovskite crystals, which catalyzes Ostwald ripening process resulting in a good quality perovskite films. High quality perovskite films are obtained when subjected to MPAT of 350 watts power for 25 seconds. The resulting films in inverted solar cell architecture shown champion efficiency of 13.39%. This is significant improved performance over devices employing films without MPAT treatment (PCE=11.5%). The MPAT paves a way to prepare high quality perovskite films that is of particularly significance for manufacturing of the large area perovskite solar cells.